An obstetric challenge in the management of lymphoma in pregnancy - Sundararajan, Chitramani; Venkadachalam, Indu; Parthasarathy, Suganya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Non-Hodgkin lymphoma (NHL) comprises of heterogeneous group of lymphoid malignancies originating from lympho-reticular tissues and is quite uncommon in pregnancy (0.8 cases per 1,00,000 women). Anaplastic large cell lymphoma (ALCL) is a large-cell neoplasm with anaplastic morphology classified under NHL. Here, a 31 year old primigravida diagnosed with NHL of ALCL subtype in third trimester, started on chemotherapy which resulted in severe pancytopenia during which she had to undergo emergency caesarean section for fetal indication. This patient was transfused with blood products and managed in isolated intensive care unit. She had a good outcome in postnatal period and went on to complete her chemotherapy and ended with remission of lymphoma.